Composite behaviour of fibre-reinforced concrete sandwich panels with FRP shear connectors. (1st November 2019) - O′Hegarty, Richard; West, Roger; Reilly, Aidan; Kinnane, Oliver
Highlights: Fibre reinforced concrete sandwich panels with foam insulation and FRP connectors are presented. Four full-height panels are tested under a 3-point loading regime. Finite element modelling is used to understand the interaction of the different components. All panels showed evidence of post cracking ductility. No evidence of composite action between the two concrete wythes was observed. Abstract: The flexural behaviour of a precast concrete sandwich panel constructed of high performance fibre reinforced concrete wythes and foam insulation, connected together with carbon fibre reinforced polymer grid connectors, is investigated in this paper. This study tests and analyses the thin concrete cladding system which omits conventional steel reinforcement, the use of which requires concrete cover to the reinforcement layer that typically dictates the minimum thickness of the concrete wythes. A total of four full height panels are constructed in a precast concrete facility and are tested by way of three point bending. To complement the experimental study, finite element analysis is used to better understand the bending behaviour beyond what was discerned from the results obtained through experimentation. The experimental results showed that the thin concrete sandwich panel is a plausible solution for precast cladding systems with ultimate moment capacities in excess of those required to meet design wind loads. Ductile behaviour was observed in all of the four tested panels as a result of the high dosage of small 24 mm coated glass fibres used in the mix design for the concrete wythes. The experimental results showed no evidence of the FRP grid connector providing any significant degree of composite action. Finite element analysis suggests that this is due to, one or a combination of, the insulation′s stiffness being too low or because the tensile members in the grid connector being under an initial compressive strain and not fully engaged during initial loading.